Wellbeing in developing countries : from theory to research - Gough, Ian; McGregor, J. Allister (Cambridge : Cambridge University Press, 2007)
This book establishes a new strategy and methodology for researching wellbeing that can influence policy.
Introduction: 1. Theorising wellbeing in international development Ian Gough, J. Allister McGregor and Laura Camfield; Part I. Human Needs and Human Wellbeing: 2. Conceptualising human needs and wellbeing Des Gasper; 3. Basic psychological needs: a self-determination theory perspective on the promotion of wellness across development and cultures Richard Ryan and Aislinn Sapp; 4. Measuring freedoms alongside wellbeing Sabina Alkire; 5. Using security to indicate wellbeing Geof Wood; 6. Towards a measure of non-economic wellbeing achievement Mark McGillivray; Part II. Resources: From Material to Cultural: 7. Wellbeing, livelihoods and resources in social practice Sarah White and Mark Ellison; 8. Livelihoods and resource accessing in the Andes: desencuentros in theory and practice Tony Bebbington, Leonith Hinojosa-Valencia, Diego Munoz and Rafael Enrique Rojas Lizarazu; 9. Poverty and exclusion, resources and relationships: theorising the links between economic and social development James Copestake; Part III. Quality of Life and Subjective Wellbeing: 10. Cross-cultural quality of life assessment: approaches and experiences from the health care field Monika Bullinger and Silke Schmidt; 11. Researching quality of life in a developing country: lessons from the South African case Valerie Moller; 12. The complexity of wellbeing: a life-satisfaction conception and a domains-of-life approach Mariano Rojas; Conclusion. Researching Wellbeing: 13. Researching wellbeing across the disciplines: some key intellectual problems and ways forward Philippa Bevan; 14. Researching wellbeing: from concepts to methodology J. Allister McGregor.
Includes bibliographical references : (page 351-386) and index.
Keywords: Basic needs -- Developing countries; Well-being.; Quality of life -- Developing countries; Quality of Life -- research